The Implementation of Collaborative Academic Supervision in Strenghening Elementary School Teacher Performance: A Qualitative Case Study in the Merdeka Belajar Era - Sri Wahyuningsih; Rina Mastikaningsih; Nurdiyati Nurdiyati; Soedjono Soedjono (FKIP - Universitas Riau, 2026)
This study is grounded in the need to strengthen elementary school teacher performance in the Merdeka Belajar era, which emphasizes autonomy, collaboration, and reflective instructional practices. The study aims to examine the implementation of collaborative academic supervision and its contribution to improving teachers’ performance. A qualitative case study approach was conducted at SD Negeri 01 Kalirejo, Talun District, Pekalongan Regency, during the first semester of the 2025/2026 academic year. Data were collected through classroom observations, in-depth interviews, documentation analysis, teacher perception questionnaires, and reflective journals. The findings show that collaborative academic supervision was implemented systematically through joint planning, classroom observation, reflective dialogue, and collegial follow-up actions, with the principal acting as a facilitator rather than an evaluator. This approach positively influenced teacher performance in lesson planning, instructional implementation, assessment practices, follow-up actions, and professional development. Teachers also demonstrated increased motivation, reflective awareness, and collaborative engagement. The novelty of this study lies in evidence that collaborative academic supervision functions as a sustainable professional learning strategy aligned with Merdeka Belajar principles framework.